Strategi Pembelajaran Tari Melalui Improvisasi Gerak untuk Meningkatkan Kreativitas Siswa SMAN 2 Blitar - Allfa Andranica Devya Aprilyawati; Robby Hidajat (Gesture: Jurnal Seni Tari, 2026)
The article describes the dance learning strategy at SMAN 2 Blitar. The researcher used a qualitative case study approach with data collected through observation, interviews, and documentation. The data credibility test applied was source and technique triangulation. Data analysis was carried out through data reduction, data presentation, and conclusion drawing. The research findings describe the application of effective dance learning strategies with movement improvisation material in dance extracurricular activities at SMAN 2 Blitar. Movement improvisation helps provide students with movement experiences, fosters movement awareness, and achieves three of the five levels of creativity, namely expressive, technical, and inventive. The contribution of this research provides and adds to a deeper understanding of the effectiveness of dance learning strategies through improvisation material. It is also hoped that it can contribute to the development of more efficient dance learning in the future.